การเตรียมไทเทเนียมไดออกไซด์เร่งปฏิกิริยาเชิงแสงเคลือบบนพอลิ (เมทิลเมทาคริเลต) สำหรับการขจัดฟีนอลจากน้ำเสีย - ฐนิสตา เลื่อนลอย (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
To study the phenol removal via photooxidation catalyzed by using titanium dioxide coated on poly(methyl methacrylate) (PMMA) sheets prepared by dip-coated technique. The effects of mole ratio of acetylacetone (ACAC) to titanium dioxide and the number of coating cycle on the characteristics and catalytic efficiency of thin film titanium dioxide on PMMA sheets were also investigated. The reaction was carried out in a glass batch reactor equipped with 15 pieces of ultraviolet (UV) lamps (9 watts/lamps) for 5 h. The initial phenol concentration was kept constant at 50 ppm (500 mL). The influence of reaction parameters on the phenol removal efficiency were statistically evaluated by a two-level factorial design experimental. The degradation of phenol depended on several parameters such as the number of titanium dioxide-coated on PMMA sheets, pH of phenol solution, initial phenol concentration, hydrogen peroxide concentration, power of UV lamp, oxygen flow rate and temperature. The experimental data exhibited that the mole ratio of ACA to titanium dioxide at 3 with 3 coating cycles. The optimum conditions were obtained from 8 sheets of titanium dioxide-coated on PMMA sheets in the phenol solution with initial concentration as 50 ppm, 5 of pH value, 0.62 M of hydrogen peroxide concentration. Under UV lamp power at 135 W and 200 ml/min of oxygen flow rate at 30℃ to reach the degradation rate constant of 7.2×10-3 min-1 (phenol removal of 91.4%).